Effect of organic mineral supplementation on the egg quality of semi-heavy layers in their second cycle of lay - Saldanha, ESPB [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Pizzolante, CC; Faittarone, ABG [UNESP]; Sechinato, A da; Molino, AB [UNESP]; Laganá, C (Fundação APINCO de Ciência e Tecnologia Avícolas, 2009)
This study was carried out to evaluate the effects of dietary trace mineral levels and sources on egg quality parameters of second-cycle semi-heavy layers. A number of 360 72-week-old layers were submitted to forced molting. Upon return of lay (83 weeks of age), birds were distributed according to a completely randomized experimental design of six treatments with six replicates of 10 birds each. The control treatment consisted of 0.10% dietary supplementation of trace minerals from inorganic sources, which was proportionally replaced by five levels (110, 100, 90, 80, 70%) of an organic trace mineral supplement containing 30, 30, 40, 6, 0.61, and 0.3 g/kg product of Zn, Fe, Mn, Cu, I, and Se, respectively. All diets contained equal protein, energy, and amino acid levels. Every 28 days of the experimental period (112 days) four eggs per replicate were collected for egg quality evaluation. The following parameters were evaluated: specific gravity, yolk, albumen and eggshell percentages, yolk index, Haugh units, and eggshell thickness and breaking strength. One sample per replicate, consisting of the pool of the yolks of three eggs collected at the end of each experimental period, was used to assess protein and mineral (Ca, P, Cu, Fe, Mn, and Zn) contents. The results were submitted to ANOVA, and means to the test of Tukey at 5% significance level. The evaluated trace mineral levels and sources did not influence any of the studied egg quality parameters. It was concluded that reducing organic trace mineral supplementation in up to 70% relative to 100% inorganic trace mineral supplementation does not affect egg parameters and therefore, can be applied to the diet of semi-heavy layers in their second cycle of lay.
Keywords: Eggshell quality; forced molting; mineral supplementation; yolk